2002
DOI: 10.1021/es015691t
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Trace Elements and PAHs by Fruit and Vegetables from Contaminated Soils

Abstract: The aims of this study were to investigate the uptake of seven trace elements and five PAHs in crop plants in order to establish advice regarding consumption of fruit and vegetables grown in soils contaminated by trace elements and PAHs. In a field experiment, vegetables were grown in two contaminated soils and in a reference soil, whereas fruits were collected from uncontaminated and contaminated private gardens. The results showed elevated levels of several trace elements and PAHs in the vegetables from cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
131
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(149 citation statements)
references
References 11 publications
14
131
3
1
Order By: Relevance
“…In addition, LMW-PAHs are more mobile in the soil and more likely to adsorb onto the root surface and easily transfer further into the root interior [25]. Our data indicated that PAH concentrations in lettuce grown on contaminated-soils were markedly high and generally similar to those values reported in the literatures [7,22]. However, PAH concentrations of this study were higher than the LMW and HMW PAH concentrations in lettuce grown on industrial contaminated soils [25].…”
Section: Discussionsupporting
confidence: 85%
“…In addition, LMW-PAHs are more mobile in the soil and more likely to adsorb onto the root surface and easily transfer further into the root interior [25]. Our data indicated that PAH concentrations in lettuce grown on contaminated-soils were markedly high and generally similar to those values reported in the literatures [7,22]. However, PAH concentrations of this study were higher than the LMW and HMW PAH concentrations in lettuce grown on industrial contaminated soils [25].…”
Section: Discussionsupporting
confidence: 85%
“…While beyond the scope of this paper, other traits and functions that might be locally important in species selection include shade and soil tolerance, including tolerance of heavy metals and other pollutants (Samsøe-Petersen et al 2002), invasive potential, cultural relevance, nitrogen fixation, nutrient density, market value, and wildlife value. Further research could make use of more extensive plant databases, including those developed by Plants for a Future (http://pfaf.org), Jacke and Toensmeier (2005:495-562), and the USDA Agricultural Research Service (2010).…”
Section: Species Multifunctionalitymentioning
confidence: 99%
“…Samples were stored in closed disposable plastic bags in a dry and dark place until analysis. Sample preparation and analytical procedures were conducted as described elsewhere (Samsoe-Petersen et al, 2002;Aras and Ataman, 2006;Ekholm et al, 2007;Vincevica-Gaile, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Anthropogenic activities can lead to an increased risk of allotment garden contamination, mainly by potentially toxic metals and metalloids such as As, Cd, Cr, Cu, Hg, Ni, Pb, Zn, etc., as well as by organic chemicals. Subsequent contamination in the food chain may affect animals or humans consuming vegetables and fruits that are grown in allotment gardens located in appropriate territories (Samsoe-Petersen et al, 2002;Goldhaber, 2003;Eggen et al, 2011;Wunderlich et al, 2011).…”
Section: Introductionmentioning
confidence: 99%